Sentidos do medo no discurso político eleitoral brasileiro contemporâneo - Sakai, Daiane Ramon Fagundes (2012)
This work aims to analyze the meanings of the word "fear" in the brazilian electoral political discourse. More precisely, based on the principles of Discourse Analysis derived from Pêcheux and his group, the aim here is to interpret statements that were generated by the major candidates for president in the Free Television Time for Election (HGPE) campaign of the years 1989, 1994, 1998, 2002 and 2006. The specific objectives refer to the discursive description and interpretation of the acting of the word "fear", and will be guided by the hypothesis that the meaning of that word will be built as it is inserted in one or another discursive formation and employed in one or another condition of production. The corpus of research is constituted based on an initial triage undertaken on all HGPEs of these presidential campaigns, through exclusive selection of statements in which the lexeme "fear" is used explicitly. In order to achieve these goals, the first chapter presents some reflections on the various facets of fear in history, focusing on biological, cultural, historical and political aspects. Then the second chapter lists some aspects of what could be a brief history of fear of the left and right in Brazil. Finally, the last chapter presents some synthetic considerations Discourse Analysis, in order to, from them, the statements contained in the word fear can be analyzed in a discursive perspective. Regardless of the ideology of the candidate, that is, right or left, it is concluded that the use of the word "fear" is present in both discourses in order of slandering the opponent, and hence manipulate the voter.